O Sistema Único de Assistência Social em Barra do Bugres/MT e a participação dos usuários - Paula, Rafaella Pereira França de (2014)
This dissertation aims to problematize the issue of participation of users of the Unified Social Assistance System (SUAS) in implementing of this system, having as parameter the legislation and norms that govern Social Assistance Policy in the national scenario, example: the Lei Orgânica da Assistência Social (LOAS), the Norma Operacional Básica (NOB/SUAS), the Política Nacional de Assistência Social (PNAS), among others. Besides, the process of participation evidenced by the empiric research in Barra do Bugres, Mato Grosso participation. Regarding the methodology, the research was based on primary and secondary sources, in the case of the latter, the main ones were: a literature search regarding the subject of study, and to documental, based on the reports of CRAS, monitoring reports of families and other documents that could contribute to contextualization of the object of study. Primary sources as semi-structured interviews with technicians and managers of his Barra do Bugres and users of basic social protection, specifically, CRAS were used. The interviews involved eight (8) technical and managers and thirty (30) users of Suas. It is about a qualitative approach to reports that allowed reports point out some tendencies as to the limits and potentialities of user participation in the spaces of the Social Assistance Policy beyond social control by means of advice, but thinking the programs and services of CRAS as spaces of participation. The content of the interviews, field observation and professional experience were compared with the theoretical buildup built up over training and construction of this dissertation process. In sum, results indicate to the need for overcome the paternalism that still insists permeate the assistance field facing the challenges that impede the Social Assistance be held as guarantor policy of universal social rights.